Alchemy and the Repair of Dissociation - a Response to William Meredith-Owen - West, Marcus (Journal of analytical psychology, 2021)
This paper is a response to William Meredith‐Owen’s paper presented at the inaugural joint conference on ‘Alchemy, a bridge to Jung’s objective psyche’, for The Society of Analytical Psychology and the West Midlands Institute of Psychotherapy in autumn 2020. The paper presents a way of understanding the collective unconscious through the functioning of the core self, and thus offers a bridge which addresses the indivisibility of the personal and collective psyche/unconscious, referencing Mary Williams’ (1963) classic paper. Specifically, this is applied to Winnicott’s dream of destruction that he had after reviewing Memories, Dreams, Reflections, as well as to parts of the psyche that were dissociated due to significant early deprivation – the primary narcissistic wounds. Alchemical metaphors are shown to relate to the analytic process, which allows the primitive core self (with its identificatory, participatory, connecting nature), when integrated through relationship, to sink back into the unconscious and function as the Self. Cet article est une réponse à l’article que William Meredith‐Owen a présenté à la conférence inaugurale commune à la Society of Analytical Psychology et l’Institut de Psychothérapie des West Midlands, à l’automne 2020, conférence intitulée « L’Alchimie, un Pont vers la Psyché Objective de Jung ». L’article présente une manière de comprendre l’inconscient collectif à travers le fonctionnement du noyau du soi, et offre ainsi une passerelle permettant de rendre compte de l’indivisibilité de la psyché/de l’inconscient collectifs et individuels, en référence à l’article bien connu de Mary Williams (1963). Plus spécifiquement, ceci est appliqué au rêve de destruction que Winnicott a eu après avoir fait la critique de « Ma vie: Souvenirs, Rêves et Pensées ». Ceci est également appliqué à des parties de la psyché qui ont été dissociées du fait de carences précoces importantes – les blessures narcissiques primaires. Il est montré que les métaphores alchimiques rendent compte du processus analytique, qui permet au noyau primitif du soi (avec sa nature identificatoire, participative et liante), quand il est intégré par le biais de la relation, de se retirer dans l’inconscient et de fonctionner en tant que Soi. Dieser Text ist eine Antwort auf den Beitrag von William Meredith‐Owen, das auf der ersten gemeinsamen Konferenz über 'Alchemie, eine Brücke zu Jungs objektiver Psyche' für die Society of Analytical Psychology und das West Midlands Institute of Psychotherapy im Herbst 2020 vorgestellt wurde. Der Artikel zeigt eine Möglichkeit auf, das kollektive Unbewußte durch die Funktionsweise des Kernselbst zu verstehen und bietet damit eine Brücke zur Unteilbarkeit der persönlichen und kollektiven Psyche/des Unbewußten und welche auf die klassischen Ausführungen von Mary Williams (1963) verweist. Dies wird insbesondere auf Winnicotts Traum von Zerstörung bezogen, den er nach Durchsicht von Erinnerungen, Träume, Gedanken hatte, sowie für Teile der Psyche, die aufgrund einer signifikanten frühen Deprivation dissoziiert waren ‐ die primären narzißtischen Wunden. Alchemistische Metaphern werden herangezogen, die sich auf den analytischen Prozeß beziehen, der es dem primitiven Kernselbst (mit seiner identifizierenden, partizipativen, verbindenden Natur), wenn es durch eine Beziehung integriert wurde, ermöglicht, ins Unbewußte zurückzufallen und als Selbst zu fungieren. Questo lavoro è stato presentato in risposta al alavoro di Meredith‐Owen per l'inaugurazione della conferenza congiunta della The Society of Analytical Psychology e del West Midlands Institute of Psychotherapy nell'autunno del 2020. L'articolo propone un modo per comprendere l'inconscio collettivo attraverso il funzionamento del Sé nucleare, e così offre un ponte che indica l'indivisibilità tra la psiche personale e collettiva e l'inconscio, facendo riferimento al classico lavoro di Mary Williams (1963). Più specificamente, questo viene applicato al sogno di distruzione che Winnicott fece dopo aver recensito Memorie, Sogni, Riflessioni, come pure vengono considerate le parti della psiche che erano dissociate a seguito di una importante deprivazione precoce –la ferita narcisistica originaria. Le metafore alchemiche vengono collegate al processo analitico, che permette al Sé nucleare originario (con la sua natura identificativa, partecipativa e di connessione), quando integrato attraverso una relazione, di reimmergersi nell'inconscio e funzionare come to Sé. Эта статья была написана в ответ на выступление Мередит‐Оуэна на инаугарационной совместной конференции Общества Аналитической Психологии и Института Психотерапии Западного Мидландс осенью 2020 года. В статье представлен способ понимания коллективного бессознательного через функционирование ядерного селф, таким образом, является связующим звеном между неделимостью личной и коллективной психики/бессознательного, упомянутой в классической работу Мэри Уильямс (1963). Особенно это касается сновидения Винникота о разрушении, которое ему приснилось после написания обзора «Воспоминания, сновидения, размышления», а также тех частей психики, которые были диссоциированы в результате значительной ранней депривации – первичные нарциссические раны. Приведены алхимические метафоры, которые показывают как аналитический процесс позволяет первичому ядерному селф погрузиться назад в бессознательное и функционировать как Самость. Это возможно при интеграции в отношения. El presente trabajo es una respuesta al trabajo presentado por William Meredith‐Owen en la Conferencia Inaugural conjunta entre la Sociedad de Psicología Analítica y el Instituto de Psicoterapia West Midlands, sobre ‘Alquimia, un Puente hacia la Psique Objetiva de Jung’, en el otoño del 2020. El trabajo presenta un modo de comprender el inconsciente colectivo a través del funcionamiento del self nuclear (‘core‐self’), y ofrece así un puente que da cuenta de la indivisibilidad de psique personal y colectiva, referenciando el clásico trabajo de Mary Williams (1963). Específicamente, se aplica al sueño de destrucción que Winnicott tuvo luego de su revisión de Recuerdos, Sueños, Pensamientos, así como a partes de la psique que fueron disociadas debido a una significativa falta temprana – herida narcisista temprana. Se muestran metáforas alquímicas relacionadas al proceso analítico, el cual posibilita al self nuclear primitivo (con su naturaleza conectora, participativa e identificatoria), hundirse en el inconsciente y funcionar como Sí Mismo, cuando es integrado a través de una relación. 炼金术及分裂的修复——对William Meredith‐Owen的回应 这篇文字回应了William Meredith‐Owen在2020年秋季, 分析心理学会与中西部地区心理治疗学院联合大会的开幕式上的论文“炼金术, 通往荣格客体心灵的桥梁”一文。文章呈现了一种通过核心的自我的功能来理解集体无意识的方法, 透过这一方式, 提供了一个可以显露出个体与集体心灵/无意识之间的不可分割性的桥梁, 这正是Mary Williams(1963)经典论文中的观点。文章特别将这一观点应用于温尼克特在回看《回忆、梦、思考》后做的破坏性的梦之上, 也应用于那些由于早期的剥夺而分裂出去——即原初的自恋创伤的心灵部分。文章呈现了炼金术的隐喻与分析过程的联系, 这一过程允许原始的核心自我 (带着它的认同性、参与性, 连接性的特征), 在透过关系整合时, 重新沉浸回无意识以及回归它作为自性的功能。